The modernization of the French civil service: crisis, change and continuity - Clark, David (1998)
This article examines the policy of Fifth Republic governments towards the modernization of the French civil service, with particular reference to the period since 1989. It has three main objectives. The first is to clarify the terms of the French debate about the crisis of the state, which is necessary to an understanding of the intellectual context of reform. The second is to describe and analyse the various strands of `administrative modernization' policy. The third is to provide an interim assessment of the impact on the structure and culture of the civil service of what is an on-going programme of administrative reform. The origins and development of modernization policy are examined from a `regulationist' perspective which emphasizes that modernization is intended to re-assert the legitimacy and effectiveness of state action, most notably by deconcentrating the management of public policies to the `local' civil service. - Reproduced
Keywords: Civil service - France; Civil service